1977
DOI: 10.1128/aem.33.4.940-946.1977
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bacterial number and biomass in the marine environment

Abstract: Three techniques for the measurement of bacterial numbers and biomass in the marine environment are described. Two are direct methods for counting bacteria. The first employs an epifluorescence microscope to view bacteria that have been concentrated on membrane filters and stained with acridine orange. The second uses a transmission electron microscope for observing replicas of bacteria that are concentrated on membrane filters. The other technique uses Limulus amebocyte lysate, an aqueous extract from the ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
164
1
8

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(190 citation statements)
references
References 11 publications
12
164
1
8
Order By: Relevance
“…The average volume of planktonic bacterial cells is generally 0.05-0.10 p,m 3 (Ferguson and Rublee 1976, Bowden 1977, Hobbie et al 1977, Watson et al 1977, Zimmerman 1977. The biomass of free bacteria available to zooplankton for the different experiments can be calculated by assuming a cell density of 1.07 g/mL, a dryto wet-mass ratio of0.23, and a carbon to dry-mass ratio of0.5 (Bowden 1977, Watson et al 1977. Calculated bacterial C biomasses were 8.6-17.2, 30.2-60.3, and 92.3-184.6 p,g/ L for the winter, spring, and summer experiments, given the above conversion factors and the range of mean cell volumes generally found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average volume of planktonic bacterial cells is generally 0.05-0.10 p,m 3 (Ferguson and Rublee 1976, Bowden 1977, Hobbie et al 1977, Watson et al 1977, Zimmerman 1977. The biomass of free bacteria available to zooplankton for the different experiments can be calculated by assuming a cell density of 1.07 g/mL, a dryto wet-mass ratio of0.23, and a carbon to dry-mass ratio of0.5 (Bowden 1977, Watson et al 1977. Calculated bacterial C biomasses were 8.6-17.2, 30.2-60.3, and 92.3-184.6 p,g/ L for the winter, spring, and summer experiments, given the above conversion factors and the range of mean cell volumes generally found.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of lake and pond carbon budgets suggest that zooplankton obtain a substantial proportion of their carbon from detritus pathways via bacteria (Wetzel 1975:611-613). Recent advances in methodology have confirmed that bacteria are both numerically abundant (Hobbie et al 1977, Watson et al 1977, Hobbie 1979, Porter and Feig 1980 and significant producers of biomass in the plankton.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large range of published values of the biovolume-to-cell-carbon ratio (volume conversion factor, or VCF) for bacteria (Table 4). Some of these factors are deduced from assumed values of the carbon-to-dry-weight (C/DW) and dry-weight-to-wet-weight (DW/WW) ratios, and the density of the cells (p) [Ferguson and Rublee, 1976;Williams and Carlucci, 1976;Hagstrom et al, 1979;Jordan and Likens, 1980;Pedros-Alio and Brock, 1982] Values of the CCQ for a range of VCF' s and cell sizes are given in Table 5. For cells larger than about 0.5/am (ESD), only the lower end of the VCF range is consistent with the community-level solutions presented in this paper.…”
Section: Least Squares Analysis Suggests a Dcml Value For M• Ofmentioning
confidence: 99%
“…In natural samples the technique most frequently used to measure volumes of bacteria has been epifluorescence [12][13][14]18,20]. There are two commonly used epifluorescence techniques: that of Zimmermann and Meyer-Reil [25] (EPI1) and that of Hobbie et al [26] (EPI2).…”
Section: Epifluorescence Versus Phase Contrastmentioning
confidence: 99%
“…Techniques currently in use include optical and electronic methods. In the first category three types of microscopy have been used most often: phase contrast [11], epifluorescence [12][13][14] and scanning electron microscopy (SEM) [7,8,15,16]. Some studies have been done comparing SEM and epifluorescence [17,18].…”
Section: Introductionmentioning
confidence: 99%